A low‐rating 40‐pulse AC–DC rectifier based on a new passive harmonic mitigation circuit - Rohollah Abdollahi; Gevork B. Gharehpetian (IET Electrical Systems in Transportation)
Abstract A novel 40‐pulse autotransformer rectifier is proposed to reduce total harmonic distortion (THD) of the input current in aircraft electrical power systems. The 40‐pulse rectifier (40PR) includes a passive harmonic reduction circuit (PHMC) with a low kVA rating (about 0.95% of the load power) to enhance the performance of the conventional 40PR. This PHMC is based on 2 harmonic suppression circuits and contains four tapped reactor and 4 auxiliary diodes. 50 Hz simulations of the improved 40PR indicate that THD of the input current and voltage is less than 2%, which meets the IEEE‐519 standard. In addition, without using any input and output filters, input current harmonic components at 400–800 Hz are less than the requirements mentioned in the DO‐160G and MIL‐STD‐704F standards. The suggested PHMC can easily be implemented. A prototype is developed to verify the proposed design. A good agreement can be seen in simulation and experimental results.